EVALUASI IMPLEMENTASI KEBIJAKAN PROGRAM PENDIDIKAN PIMPINAN TINGKAT NASIONAL PADA LEMBAGA KETAHANAN NASIONAL REPUBLIK INDONESIA - Rusmali Anggawiria (Jurnal Manajemen Pendidikan, 2016)
National Resilience Institute Republic of Indonesia as education providers focus on the education program cadreled national level, the appropriate duties and functions of educating, preparing cadres and strengthen the leadership of the national level through educational programs, so that the necessary preparation of the infrastructure of education, educational operations, development of educational materials and teacher. In this paper focuses on policy implementation leadership education programs with sub-national level focus include: 1). Supporter infrastructure management education. 2). Preparation of Educational Material. 3) .Governance / educational operations. 4). Performance faculty or holder teachings material. In the evaluative research using the model Discrepancy Evaluation Model (DEM), through the stages of Design Stage, Installed Programs, Process and Product. Based on the evaluation of research in the field, the researcher recommends 1). The need to increase both the quality and quantity of Infrastructures Education. 2). The need to increase the quality and ease of getting material Doctrine. 3). Operational management of the need to improve education. 4). The need to improve the appearance and teaching methods in the aspect of teaching staff personnel and Manpower Professional reviewers. National Resilience Institute of Republic of Indonesia is the appropriate institution be a leading sector in implementing the mental revolution because during this time the duties and functions of the Indonesian National Resilience Institute will educate the nation's leading cadres both from the political parties, the government and private sectors.